Poly(vinyl butyral) -polyaniline-magnetically functionalized fly ash cenosphere composite film for electromagnetic interference shielding. (1st December 2016) - Bora, Pritom J.; Mallik, Nitin; Ramamurthy, Praveen C.; Kishore,; Madras, Giridhar
Abstract: The present study is about the electromagnetic interference (EMI) shielding effectiveness of polymer-magnetically functionalized industrial waste fly ash cenosphere (FAC, hollow microspheres) composite film. The size range of the used FAC was 5–70 μm (average size ∼ 45 μm) and these were Co/Ni coated chemically and efficiently functionalized by in situ synthesis of polyaniline under nitrogen at −30 ± 2 °C. Poly(vinyl butyral)–polyaniline-Co/Ni-FAC composite films (PVB-PANI-Ni/Co-FAC) were prepared by solution processing and electromagnetic interference (EMI) shielding property was investigated in the J-band (5.8–8.2 GHz) and X-band (8.2–12.4 GHz) frequency range. The most effective EMI shielding effectiveness (SE) of ∼20 ± 1 dB and ∼23 ± 1 dB was obtained for PVB-PANI-Ni-FAC (PVBPNC) film (thickness 259 ± 2 μm) in the frequency range 5.8–8.2 GHz and 8.2–12.4 GHz respectively, whereas EMI SE of PVB-PANI film (268 ± 2 μm) was found to be ∼11 ± 0.52 dB and ∼13 ± 1 dB. For all the composite films, majority of EMI shielding occurs due to the absorption. The obtained EMI shielding due to absorption (SEA ) of PVBPNC film was found to be ∼17 ± 1 dB and ∼20 ± 0.53 dB for J-band and X-band, respectively. In contrast to PVB-PANI (PVBP) film the SEA of PVB-PANI-Co/Ni-FAC composite film was found to increase with frequency. This behaviour of these composite films is exchanged as due to the increase of frequency dependent conductivity and EM attenuation constant. The dielectric studies, also carried out in this investigation, calculated complex permittivity ( ε ∗ = ε ′ − i ε ″ ), and complex permeability ( μ ∗ = μ ′ − i μ ″ ) values show the excellent electrical ( ε″ ) and magnetic loss ( μ″ ) for enhancing the EMI shielding due to absorption.